The morphological, physiological, and anatomical responses of temperate trees to climate change and their greenhouse gas emissions - Abubakar, Abdulrazaq Iliya (2025)
The exchange of carbon, water, and energy between land and atmosphere is driven by plant physiological processes yet few studies have examined temperate tree saplings' physiological responses to climate change. Here we assessed the response of plant physiology and biomass of tree sapling waterlogging and either the interaction between elevated temperature and elevated CO2 in a two-year growth room experiment with saplings of Alnus glutinosa, Betula pendula, Betula pubescens, Salix pentandra and Salix aurita. In the temperature experiment, waterlogging increased photosynthesis, stomatal conductance, and transpiration rates in A. glutinosa and S. pentandra. Elevated temperature increased the photosynthesis, stomatal conductance, and transpiration rates for Betula pendula but Alnus glutinosa decrease photosynthesis, stomatal conductance and transpirations rates. In the CO2 experiment, there was a contrasting response to waterlogging among the species. Photosynthesis, transpiration and stomatal conductance increased for B. pendula but decreased for B. pubescens. Elevated CO2 increased photosynthesis, transpiration and stomatal conductance A. glutinosa and B. pubescens. There was increase in total dry root biomass specifically under waterlogging in both species under elevated temperature and CO2. Our results suggest that rising temperatures, CO₂ levels, and waterlogging will differentially impact plant physiology across tolerant and sensitive species, with significant implications for future vegetation dynamics and ecosystem functioning in temperate systems under climate extremes.